Interpreting visual culture : explorations in the hermeneutics of the visual - Heywood, Ian, 1948-; Sandywell, Barry (Routledge, 1999)
Ranging from an analysis of the role of vision in current critical discourse to discussion of examples taken from the visual arts, ethics and sociology, this collection presents material on the interpretation of the visual in modern culture.